ANALISIS ENVIRONMENTAL AWARENESS VALUE DAN GREEN PRACTICES TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Juliana Juliana; Amelda Pramezwary; Arifin Djakasaputra; Jessica Novia Widjaja; Jessica Virgiana Wijaya (Jurnal Sociohumaniora Kodepena (JSK), 2021)
Food and Beverage products or food and beverages are growing and growing rapidly. However, plastic becomes the raw material of F&B packaging until now is still a pro cons due to the health influence of the chemicals contained in it and not environmentally friendly. The environmental damage is now getting worse and has raised concerns. As knowledge increases, consumers increasingly know how to spend their money. Environmental Awareness value and Green Practices are considered by consumers to make a purchasing decision on a product. The purpose of this study was to analyze the influence of Environmental Awareness value and Green Practices on Consumer Purchasing Decisions on F&B Products. Research was conducted online by distributing questionnaires through google forms to 96 respondents using descriptive quantitative analysis methods and data analysis using multiple linear regression tests, determination coefficient tests and F tests and t tests, which were processed with the SPSS program. The results showed that Environmental awareness value and green practices showed a positive and significant influence on consumer purchasing decisions on F&B Products. Key Words: Environmental Awareness value , Green Practices, Purchase Decision